Improved over Modulation Strategy in DTC with Constant Frequency Torque Controller of PMSM for Quick Torque Control at Different Dynamic Conditions - Alsofyani, Ibrahim Mohd; Lee, Kyo Beum (2018 IEEE Energy Conversion Congress and Exposition, ECCE 2018, 2018)
This paper proposes an improved dynamic overmodulation for direct torque control with constant switching frequency controller (DTC-CFTC) of AC motor drives to achieve fast dynamic performance under different operating conditions. The dynamic process of the DTC is obtained by the selection of active voltage vectors in the torque trainset. To further improve the dynamic performance, the most optimized active voltage is identified and selected based on the flux position. However, owing to the nature of the DTC-CFTC, some zero voltage vectors are selected in the dynamic process. As such, with the optimized voltage vector, the torque performance of DTC-CFTC is still slow. By simultaneous modification of torque and flux error statuses, the proposed overmodulation strategy can overcome this problem and achieve very fast torque response at different speed and torque operations. The effectiveness of the proposed overmodulation in DTC-CFTC of PMSM is verified by simulation results.
Keywords: Constant switching frequency; Different operating conditions; Direct torque control; Discontinuous PWM; Dynamic performance; Fast torque response; Switching loss; Zero voltage vectors; Discontinuous PWM; Switching losses